Evaluasi Usability Tampilan Antarmuka Website Perpustakaan Politeknik Kesehatan Kemenkes Kota Malang menggunakan Metode Usability Testing dan Heuristic Evaluation - Arnezha Tinar; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Library of Health Polytechnic of Malang City Health Ministry has an official website to help students find references to study. This website has a search feature for a collection of textbooks, national, international journals and lecturer research. Based on observations, there are complaints on the website, namely, ineffective and inefficient search, inappropriate use of words and no library book lending information. This study uses the usability testing and heuristic evaluation methods because the heuristic evaluation method is able to find many usability problems so that all usability problems can be resolved. This research combined with usability testing to get the user's perspective. Determination of evaluators using regular and double because the potential for finding problems is higher than the novice evaluator. Based on the results of the evaluation using the usability testing method and heuristic evaluation obtained 26 usability problems. 23 usability problems from heuristic evaluation and 6 usability problems from usability testing. Problems that are found are mostly related to the functionality and appearance of the system interface. Usability testing produces a level of effectiveness of 60%, efficiency of 46.5% and satisfaction of 63.4. The usability problem found in heuristic evaluation is divided into 7 out of 10 Nielsen's heuristic principles. The most common usability problems found on the principle of H8 aesthetic and minimalist design are 9 usability problems. Usability problems found have 1 usability problems in the cosmetic category, 11 usability issues in the minor category, 3 usability issues in the medium category, 2 usability issues in the major category, and 6 usability problems in the catastrophic category.